Challenges for implementing liveable communities in Bangsar, Kuala Lumpur - Ang, Siew Teng; Syed Salim, Azizah Salim (Universiti Putra Malaysia, 2012)
Liveability refers to the health and social quality of an area as perceived by all stakeholders in study area. Bangsar is a residential area which comprised of different level of social classes. Therefore liveability level in Bangsar communities also varies due to its existing condition of public realm in different areas and diversity group of people. Hence implementation of liveable communities in Bangsar is not achievable as a whole. Every community in Bangsar has its own common barrier for implementing liveable communities. Therefore there is a need to examine existing community liveability and common barrier for achieving desired level of liveability in Bangsar. The important key elements in liveable community such as physical structures, natural features and service provisions are examined to understand what constitute a liveable community. The urban morphology and survey research method are used to identify and evaluate the liveability in Bangsar's community. It is carried out to examine the challenges for creating liveable communities and real needs of the residents towards liveable community in Bangsar. The outcome of this study is potential to use as a resource that can assist the urban planning industry in Kuala Lumpur to incorporate health and social outcome in new proposed development.